Evaluation of the Effectiveness and Efficiency of the Government Regulation Implementation Number 12 of 2019 - Icuk Rangga Bawono; Adhitia Pradana; Apriani Kartika Rahayu (Jurnal Hukum Prasada, 2021)
The law should govern the dynamics of the nation and state life in an ideal country. For instance, Indonesia is a constitutional state that subjects to legal supervision based on the 1945 Constitution for state administration. Public policies are used as guidelines and references for actions, including financial management. However, regulations as the basis for regional financial management need to be adjusted to suit the dynamics in legal condition development and the community needs. Government Regulation Number 12 of 2019 is an improvement to Government Regulation Number 58 of 2005 on Regional Financial Management used as a reference in formulating regional financial management rules. This study examines the evaluation of the readiness to implement Government Regulation Number 12 of 2019 as the basis for regional financial management. The method used in this study is a normative legal research method. The legal materials source from primary and secondary legal material. The method in presenting this research result is deductive method. This study shows that financial management is a government responsibility in exercising regional power. The urgency of drafting a Regional Regulation on financial management is motivated by changes in legal dynamics and community needs for its management. Furthermore, there is a need for evaluation of the regulation improvement for effectiveness. In conclusion, the effectiveness and efficiency of regional financial management should be evaluated after Government Regulation Number 12 of 2019 is applied. The regulations need to be disseminated for the wider community response to be identified for evaluation of improvements and adjustments to its needs.